The Role of MR Imaging and MR Angiography in the Evaluation of Patients with Headache - Pavlović, Tomislav; Trtica, Sanja; Milošević, Marina; Budinčević, Hrvoje; Borić, Igor (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Headache is one of the most common complaint in medical practice and the most often neurological symptom. AIM: The aim of our study was to estimate the frequency of abnormal magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) findings in patients with non-acute headache without focal neurological abnormalities. MATERIAL AND METHODS: The results of the MRI and MRA were retrospectively analyzed. As major abnormalities, we took into account tumor, stroke, extraaxial collection, Chiari malformations, and vascular pathology (aneurysm and arterial-venous malformation). RESULTS: Two hundred twenty-five patients fulfilled the criteria. Out of 225 patients with median age of 37 (18–85) years, 78% of the patients were female and 22% were male. In total, we found 8.4% of major abnormalities. On MRI head scan without MRA analysis, we found 50.7% of normal finding, 47.1% of minor abnormalities and 2.2% of major abnormalities. On MRA scan, we found we found 52.9% of normal finding, 40.9% of minor abnormalities, and 6.2% of major abnormalities. CONCLUSION: Our study demonstrates a low but important diagnostic yield of MRI and MRA examination for patients with non-acute headache without focal neurological abnormalities.